VP129 Social Cost Benefit Analysis (SCBA) Of Three Alcohol Policy Measures. (2017) - de Wit, Ardine; van Gils, Paul; Over, Eelco; Lokkerbol, Joran; Smit, Filip; Mosca, Ilaria; Spit, Wim; de Kinderen, Reina; Evers, Silvia
Abstract : INTRODUCTION: Alcohol abuse and addiction lead to a high disease burden for the persons concerned. Moreover, it has economic consequences for society, including costs of health care, costs due to reduced productivity, criminal activities, traffic accidents, and violence, both in private and public domains. The aim of this study was to perform a social cost-benefit analysis (SCBA) of three policy measures (tax increase, reducing number of sales venues, and advertising ban) over a period of 50 years, along with the distribution of costs and benefits among stakeholders (1). METHODS: The analysis follows Dutch guidelines for performing SCBAs. Costs and benefits in eight different domains were comprehensively identified. Model simulations were used to estimate future social costs and benefits of three policy measures, compared to not intervening. RESULTS: Over a period of 50 years, the greatest social benefits were expected from a tax increase. The cumulative discounted net monetary benefit over a period of 50 years is EUR12 billion (95 percent Confidence Interval, CI EUR11-EUR13billion) in the 50 percent tax increase scenario. The net benefits of the other two measures are smaller. The cumulative discounted value to society of a 10 percent decrease in outlet density over a 50-year period amounts to EUR4 billion (range: EUR3 - EUR5 billion). A total media ban with an estimated reduction of 4 percent in alcohol consumption leads to an expected cumulative discounted value to society over a 50-year period of EUR7 billion. CONCLUSIONS: All policy scenarios lead more or less to positive effects for society. The greatest benefits are associated with measures aimed at raising the excise tax on alcohol. Estimations as made in this study may serve to inform alcohol policy in the Netherlands.